Microarray analysis of circulating micro RNAs in the serum of patients with polymyositis and dermatomyositis reveals a distinct disease expression profile and is associated with disease activity - Misunova, Martina; Salinas-Riester, Gabriela; Luthin, Susanne; Pommerenke, Claudia; Husakova, Marketa; Zavada, Jakub; Klein, Martin; Plestilova, Lenka; Svitalkova, Tana; Cepek, Pavel; Novota, Peter; Vencovsky, Jiri (Clinical and experimental rheumatology, 2016)
OBJECTIVES: The aim of this study was a large scale investigation of myositis-associated circulating miRNA molecules and also determination of expression of these candidate molecules in relation to clinical activity of myositis. METHODS: RNA, containing also miRNAs, was isolated from sera of 28 patients suffering from idiopathic inflammatory myopathies (IIM) and 16 healthy controls. Expression of miRNAs was determined using a miRNA microarray method. Statistical analysis of miRNA expression was carried out using Arraystar software. RESULTS: Our results showed 23 significantly differentially expressed miRNAs. Six miRNAs were differentially expressed in IIM compared to healthy controls. In dermatomyositis (DM) we found 3 and in polymyositis (PM) 6 differentially expressed miRNAs compared to controls. Three miRNAs were up-regulated in patients with highly active disease compared to patients with low disease activity. Furthermore, we found 26 significantly differentially expressed miRNAs in SLE patients compared to IIM, DM and PM patients. CONCLUSIONS: This is the first study that comprehensively describes expression levels of circulating miRNAs in serum of patients suffering from IIM. It can be expected that some of these deregulated miRNA molecules are involved in aetiology of IIM and may potentially serve as molecular markers for IIM development or for monitoring of disease activity.
Keywords: Software; software; Humans; dermatomyozitida; Case-Control Studies; lidé středního věku; regulace genové exprese; Oligonucleotide Array Sequence Analysis; studie případů a kontrol; MicroRNAs; Predictive Value of Tests; genetické markery; Female; dospělí; Phenotype; lidé; Dermatomyositis; Adult; ženské pohlaví; Gene Expression Regulation; stupeň závažnosti nemoci; Male; Middle Aged; prediktivní hodnota testů; fenotyp; Genetic Predisposition to Disease; genetická predispozice k nemoci; stanovení celkové genové exprese; Genetic Markers; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Severity of Illness Index; mikro RNA; Gene Expression Profiling; mužské pohlaví